GENDER CONSTRUCTION IN BUGINESE WEDDING: UANG PANAIK AND ROMANTIC LOVE AS A HYBRID CULTURE - Rafika Syahdina; Samsul Maarif; Katrin Bandel (Universitas Islam Negeri Alauddin Makassar, 2022)
This research aims to examine how Uang Panaik, the required amount of money to finance a wedding ritual/party, is negotiated against gender construction through romantic love and hybrid culture. This research focuses on Uang Panaik tradition that is practiced by Buginese as one of the requirements of a marriage. The main subjects of this research are two couples who experienced a love relationship before their marriage with love expression within the boundary of Islamic rules and their relatives. The data collection was done in two ways, the first was through interviews and the second was examining textual sources relevant to the topic. The data were then compared in order to see the similarity or difference between the written traditional practice of Buginese wedding ritual and the experience of the subjects. The data were analyzed by using qualitative methods with romantic love theory by Eva Illouz and hybridity theory by Homi K Bhabha. By using the theory of romantic love and hybridity, this research observes the relation between the tradition of Uang Panaik and romantic love as a hybrid culture. This research argues that the practice of Uang Panaik in Buginese wedding ritual has been reconstructed differently from the traditional ways as the practice of Uang Panaik tradition is challenged by the involvement of romantic love relationships that happened before marriage (courtship, pacaran). Thus the process of negotiating Uang Panaik against gender construction happened in a hybrid culture together with romantic love bounded by religious ethics.